Lamotrigine and Lithium Combination for Treatment of Rapid Cycling Bipolar Disorder: Results From Meta-Analysis - Zhihan, Gao; Fengli, Sun; Wangqiang, Lv; Dong, Shen; Weidong, Jin (Frontiers in Psychiatry, 2022)
Objective: to observe effect of combination of lithium and lamotrigine in treatment for Rapid-cycling bipolar disorder(RCBD). Method:We searched both MEDLINE, EMBASE, Cochrane Library in English and CBM, CNKI , WANFANG and CSSCI in Chinese to find literature from January 1 2000 to December 31, 2020 related to combination of lithium carbonate and lamotrigine for treatment of RCBD.Results:Five comparison studies, with 265 subjects of 131 cases in study group and 134 cases in control group met the inclusion criteria and were included for the final meta-analysis. The comprehensive analysis show that study group had significant lower score of mental symptoms than that of control group(Z=2.34,P=0.02) by random model(X2=33.02,df=7,P<0.01).But these differences only were shown in PANSS(Z=5.18,P<0.01) and BPRS(Z=3.08,P<0.01).The no difference in response rate ( 54.9% vs 45.7%OR=1.47,95% CI: 0.79~2.73, Z=1.21,P> 0.05, )and remission rate (47.9% vs 45.9%OR=1.05,95% CI: 0.49~2.25, Z=0.13,P> 0.05, )were found between two groups. The response rate of lamotrigine and lithium combination was significant higher compare to monotherapy of lithium in patients with no treatment-resistant(82% V 54%,OR=4.26,95% CI: 1.65~10.99, Z=3.99,P< 0.01) by fixed effect model(X2=0.89,df=1,P>0.05,I2 =0%).Conclusion:Combination of lithium and lamotrigine have better improvement of psychotic symptoms and higher response rate in patients of RCBP with no treatment-resistant.